Potential schistosome-vector snails and associated trematodes in ricefields of Corrients province, Argentina: preliminary results - Alejandra Rumi; Monika Ines Hamann (Memorias do Instituto Oswaldo Cruz, 1990)
Considering the possibility of introduction of schistosomiasis mansoni into Argentina as a consequence of dam construction on the Rio De La Plata basin, preliminary studies have been carried out on agrosystems such as ricefields in Corrientes province with the following purposes: 1) to survey and estimate the relative abundance of planorbids and identify potential vector species; 2) to identify environmental factors capable of influencing Biomphalaria population dynamics; and 3) to find out snail-parasite associations and estimate snail infection rates in order to detect possible competitive interactions between larval stages of native trematodes that could be used in biological control of Schistosoma mansoni. Three potential schistosome vectors were detected in ricefields, namely Biomphalaria straminea, B. tenagophila and B. peregrina, although B. orbignyi, a species refractory to infection with S. mansoni, proved the most frequent and abundant. Positive correlations (P<0.05) were found between Biomphalaria abundance and some environmental parameters: conductivity, hardness, calcium, nitrites plus nitrates, ammonium and bicarbonates. Water temperature correlation was negative (P<0.05). No correlation (P>0.05) was found in total iron, phosphates (SRP), pH and soil granulometry. Echinocercariae developed from rediae and belonging to Petasiger sp., Paryphostomum sp., and other undetermined species were found.